Antistatic agent for glass fibers and sizing agent for glass fibers containing the same
A high-concentration liquid quaternary ammonium salt combined with a sizing agent and other additives addresses the insufficiency of conventional antistatic agents, enhancing antistatic performance and preventing coloration in glass fibers, resulting in improved resin molded products.
Patent Information
- Application Number
- JP2020219889
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-29
- Publication Date
- 2024-12-25
- Estimated Expiration
- 2040-12-29
AI Technical Summary
Conventional quaternary ammonium salts used as antistatic agents for glass fibers do not provide sufficient antistatic effect and cause coloration of glass fibers at high temperatures, necessitating the use of large amounts to achieve desired performance.
A high-concentration liquid quaternary ammonium salt is used to enhance surface transfer during drying, combined with a sizing agent, film forming agent, lubricant, and silane coupling agent to improve antistatic properties while minimizing coloration.
The solution provides excellent antistatic performance without significant coloration, ensuring good appearance of resin molded products.
Smart Images

Figure 0007606346000001 
Figure 0007606346000002 
Figure 0007606346000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an antistatic agent for glass fibers and a sizing agent for glass fibers. [Background technology]
[0002] Glass fibers are widely used as reinforcing fibers in the manufacture of fiber-reinforced plastics (FRP) and fiber-reinforced cement products. A sizing agent is applied to glass filaments (single glass fibers) drawn from a bushing (a spinning die for molten glass) to bundle a predetermined number of filaments, which are then wound up into glass strands (glass fiber bundles). These are then heated and dried, and processed into glass fiber products such as rovings (glass strands wound into a cylindrical shape), chopped strands (glass strands cut to a predetermined length), and chopped strand mats (chopped strands laminated and formed into a mat).
[0003] In the manufacturing process of glass fibers, static electricity is easily generated, which may cause an obstacle to the work. For example, static electricity generated in the cutting process of glass strands can cause the cut material to adhere to the cutter and the cutting performance to decrease in a short time. For this reason, in order to prevent the generation of static electricity, a method has been adopted in which an antistatic agent is added to a sizing agent or an antistatic agent is applied between the production of glass strands and the cutting. As such antistatic agents for glass fibers, quaternary ammonium sulfates such as lauryl dimethyl ethyl ammonium ethyl sulfate and octyl dimethyl ethyl ammonium ethyl sulfate are used (see Patent Documents 1 to 4). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Special Publication No. 62-42870 [Patent Document 2] Special Publication No. 5-30780 [Patent Document 3] JP 2015-113256 A [Patent Document 4] JP 2017-206787 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, these conventional quaternary ammonium salts do not have sufficient antistatic effects, and in order to obtain the desired antistatic effects, a large amount of antistatic agent must be used. In addition, conventional quaternary ammonium salts have the drawback of causing coloring of glass fibers at high temperatures, and coloring of glass fibers at high temperatures such as during the drying process in the glass fiber manufacturing process is a problem. Due to the above problems, there has been a demand for the development of an antistatic agent that exhibits sufficient antistatic performance and does not cause coloring of glass fibers. The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide an antistatic agent for glass fibers that can reduce static electricity generated during processing of glass fibers and can produce resin molded articles with good appearance. [Means for solving the problem]
[0006] The inventors came up with the idea of using a highly concentrated liquid quaternary ammonium salt to facilitate migration of the salt to the surface of the glass strand together with moisture when the strand is dried, thereby improving the antistatic properties, and thus completed the present invention.
[0007] That is, the present invention is as follows. [1] An antistatic agent for glass fibers, comprising a quaternary ammonium salt represented by the following general formula (1): [ka] (In the formula, R 1 represents an alkyl or alkenyl group having 8 to 22 carbon atoms; R 2 R represents an alkyl group having 1 to 3 carbon atoms, m and n represent the average number of moles of ethyleneoxy groups added, and each is independently a number of 0.5 to 10. 3represents an alkyl group having 1 to 3 carbon atoms. [2] The antistatic agent for glass fibers according to [1], which is liquid at room temperature. [3] A sizing agent for glass fibers, comprising the antistatic agent for glass fibers according to [1] or [2]. [4] The glass fiber sizing agent according to [3], further comprising a coating agent, a lubricant, and a silane coupling agent. [5] A glass fiber having a plurality of glass fiber monofilaments and a coating formed by applying the glass fiber sizing agent according to [3] or [4] to the glass fiber monofilaments. [6] A resin molded product comprising the glass fiber according to [5] and a thermosetting resin. Effect of the Invention
[0008] According to the present invention, it is possible to provide an antistatic agent for glass fibers which exhibits excellent antistatic performance and causes little coloring of glass fibers even after exposure to high temperatures. The present invention also provides a sizing agent for glass fibers containing the antistatic agent. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The following describes the embodiments of the present invention. Not limited to this.
[0010] [Antistatic agent for glass fibers] The antistatic agent for glass fibers used in the present invention contains a quaternary ammonium salt represented by the following general formula (1). [ka] (In the formula, R 1 represents an alkyl or alkenyl group having 8 to 22 carbon atoms; R 2 R represents an alkyl group having 1 to 3 carbon atoms, m and n represent the average number of moles added, each of which is independently 0.5 to 10. 3represents an alkyl group having 1 to 3 carbon atoms.
[0011] Specific examples of the alkyl group having 8 to 22 carbon atoms include an n-octyl group, an n-decyl group, a dodecyl group (lauryl group), a tridecyl group, a tetradecyl group (myristyl group), a hexadecyl group (palmityl group), an octadecyl group (stearyl group), an eicosyl group, a docosyl group (behenyl group), and a tetracosyl group. Specific examples of the alkenyl group having 8 to 22 carbon atoms include an octenyl group, a nonenyl group, a decenyl group, a dodecenyl group, a tridecenyl group, a tetradecenyl group, a pentadecenyl group, a hexadecenyl group, a heptadecenyl group, an octadecenyl group, an eicosenyl group, a docosenyl group, and a tetracosenyl group, which may have a branched structure or a cyclic structure. Among these, from the viewpoint of imparting appropriate antistatic properties, alkyl or alkenyl groups having 8 to 18 carbon atoms are preferred, with dodecyl, isotridecyl, tetradecyl, hexadecyl and octadecyl groups being particularly preferred.
[0012] In general formula (1), m and n represent the average number of moles of ethylene oxide added, and from the viewpoint of the quaternary ammonium salt being liquid at a high concentration and migrating to the surface of the strand to improve antistatic performance, each of them is independently 0.5 or more, and preferably 1.0 or more, and from the same viewpoint, 10 or less, preferably 5 or less, and more preferably 3 or less. Moreover, from the viewpoint of improving antistatic performance, m+n is 1 or more, and preferably 1.5 or more, and from the same viewpoint, 20 or less, preferably 5 or less, and more preferably 3 or less.
[0013] R in general formula (1) 2 and R 3 represents an alkyl group having a carbon number of 1 to 3. Examples include a methyl group, an ethyl group, and a propyl group, and the most preferred is an ethyl group.
[0014] There is no particular limitation on the method for producing the quaternary ammonium salt used in the present invention, but it can be produced by reacting a polyoxyethylene aliphatic amine obtained by adding ethylene oxide to an aliphatic amine with a dialkyl sulfate.
[0015] Examples of polyoxyethylene aliphatic amines include, but are not limited to, one or more aliphatic amines selected from the group consisting of octyldiethanolamine, decyldiethanolamine, lauryldiethanolamine, myristyldiethanolamine, palmityldiethanolamine, stearyldiethanolamine, and oleyldiethanolamine, coconut alkyldiethanolamine, polyoxyethylene cocoamine, and polyoxyethylene tallow alkylamine.
[0016] Examples of dialkyl sulfates include, but are not limited to, dimethyl sulfate, diethyl sulfate, and dipropyl sulfate.
[0017] The reaction temperature when reacting a polyoxyethylene aliphatic amine with a dialkyl sulfate is, from the viewpoint of rapidly progressing the reaction, preferably 50° C. or higher, more preferably 60° C. or higher, and preferably 100° C. or lower, more preferably 90° C. or lower, and even more preferably 80° C. or lower.
[0018] The reaction molar ratio of polyoxyethylene aliphatic amine (a) to dialkyl sulfate (b) is preferably (a) / (b)=0.1 to 1.2, more preferably 0.5 to 1.0, and even more preferably 0.7 to 1.0. In particular, when the reaction molar ratio is 1.0 or less, the viscosity of the reaction product is lowered due to the influence of unreacted compounds, and the reaction product migrates to the surface, making the antistatic effect more effective, which is preferable.
[0019] If the reaction product containing a quaternary ammonium salt is in a solid or gel state at room temperature, the antistatic properties are insufficient, so it is preferable that the reaction product is in a liquid state at room temperature. In this case, room temperature is 25°C.
[0020] The antistatic agent for glass fibers of the present invention may be blended with a sizing agent or may be directly applied to glass strands. In either case, it is possible to impart excellent antistatic properties to the glass strands.
[0021] [Glass fiber sizing agent] When the antistatic agent for glass fibers of the present invention is used by adding it to a sizing agent, the sizing agent is not particularly limited, and a commonly used sizing agent may be used depending on the type of glass fiber and its application. The sizing agent is usually an aqueous liquid containing 1 to 20 parts by mass of a film-forming agent such as a starch-based, cellulose-based, or synthetic resin emulsion-based agent. When the antistatic agent for glass fibers of the present invention is used by adding it to a sizing agent, the amount added is preferably 0.5 to 20 parts by mass, more preferably 1 to 15 parts by mass, and even more preferably 3 to 10 parts by mass, based on 100 parts by mass of the active ingredient of the film-forming agent. That is, if the amount of the antistatic agent added is too small, the antistatic property cannot be fully exhibited, and conversely, if it is too large, the antistatic property may be saturated and the sizing property of the glass strand may be reduced.
[0022] As the film-forming agent of the bundling agent to which the antistatic agent for glass fibers of the present invention is added, from the viewpoint of antistatic effect, a synthetic resin emulsion-based film-forming agent is preferable. Examples of the synthetic resin emulsion-based film-forming agent include polyvinyl acetate emulsion, vinyl acetate / (meth)acrylic acid ester copolymer emulsion, ethylene / vinyl acetate copolymer emulsion, poly(meth)acrylic acid ester emulsion, epoxy resin emulsion, urethane resin emulsion, etc.
[0023] When the antistatic agent for glass fibers of the present invention is added to a sizing agent, it may contain other additives such as a silane coupling agent, a lubricant, a surfactant, etc.
[0024] Examples of the silane coupling agent include vinyl-based silanes such as vinyltrichlorosilane, vinyltris-β-methoxyethoxysilane, and vinyltriethoxysilane; amino-based silanes such as aminomethyltriethoxysilane, aminopropyltrimethoxysilane, diaminopropyldiethoxysilane, triaminopropylethoxysilane, and γ-aminopropyltriethoxysilane; methacryloxy-based silanes such as γ-methacryloxypropyltrimethoxysilane; epoxy-based silanes such as β-3,4-epoxycyclohexylethyltrimethoxysilane and γ-glycidoxypropyltrimethoxysilane; and mercapto-based silanes such as γ-mercaptopropyltrimethoxysilane. The amount of the silane coupling agent is about 0.2 to 20 parts by mass relative to 100 parts by mass of the active ingredient of the film-forming agent in the bundling agent.
[0025] Examples of lubricants include aliphatic hydrocarbons such as paraffin wax, aliphatic alcohols such as lauryl alcohol, palmityl alcohol, stearyl alcohol, aliphatic amides such as palmitic acid amide, stearic acid amide, fatty acid esters such as butyl stearate, octyl stearate, fatty acid triglycerides, etc. The amount of the lubricant to be blended is about 0.5 to 10 parts by mass per 100 parts by mass of the active ingredient of the film-forming agent in the bundling agent.
[0026] Examples of the surfactant include polyoxyalkylene alkyl ether, polyethylene glycol propylene oxide adduct, polypropylene glycol ethylene oxide adduct, glycerin fatty acid ester or its ethylene oxide adduct, sorbitan fatty acid ester or its ethylene oxide adduct, alkyl polyglucoside, fatty acid monoethanolamide or its ethylene oxide adduct, fatty acid diethanolamide or its ethylene oxide adduct, sucrose fatty acid ester, polyglycerin fatty acid ester, polyethylene glycol fatty acid ester, fatty acid methyl ester ethoxylate, weak acid salt of partial fatty acid amide of polyethylene polyamine, etc. The amount of the surfactant to be blended is about 0.2 to 20 parts by mass per 100 parts by mass of the active ingredient of the film-forming agent in the bundling agent.
[0027] When the antistatic agent for glass fibers of the present invention is applied directly to glass strands without being mixed with a sizing agent, the step of applying the antistatic agent is preferably performed after the application of the sizing agent to the glass strands, and more preferably after the glass strands are dried and before the glass strands are cut. In this case, it is preferable to apply the antistatic agent as an aqueous solution of 1 to 50 parts by mass. The amount of the antistatic agent applied to the glass strands is preferably 0.005 to 0.5% by mass relative to the glass strands. The aqueous solution of the antistatic agent may also contain the above-mentioned lubricant and surfactant.
[0028] [Glass fiber] The glass fiber of the present invention is characterized by having a plurality of glass fiber monofilaments and a coating formed by applying the above-mentioned glass fiber sizing agent to the glass fiber monofilaments.
[0029] The glass fiber of the present invention is obtained, for example, as follows. First, molten glass is drawn from a number of nozzles provided at the bottom of a platinum bushing to form 30 to 6,000 glass fiber monofilaments. Next, the above-mentioned glass fiber sizing agent is applied to these glass fiber monofilaments by an applicator or the like, and these glass fiber monofilaments are gathered into one bundle by a gathering shoe to form a glass fiber strand, which is then wound up on a collet to form a cake. Then, the cake is placed in a dryer, and the solvent (volatile matter) contained in the glass fiber sizing agent is evaporated at 80 to 130° C. for about 1 to 30 hours to form a solid film that covers the surface of the glass fiber monofilaments. This results in the glass fiber wound up on the cake.
[0030] The dried glass fibers are pulled out of the cake and cut into lengths of about 1 to 40 mm to become chopped strands.
[0031] As the glass constituting the glass fiber, glass having any composition such as E glass, A glass, S glass, D glass, NCR glass, NE glass, etc. can be used.
[0032] The glass fiber monofilament constituting the glass fiber of the present invention can be uniformly mixed with the chopped strands and the thermosetting resin in the BMC method as long as it has a fiber diameter of 3 to 30 μm. The average diameter of the glass fiber monofilament may be measured by an optical microscope or a laser measuring device.
[0033] The glass fiber of the present invention preferably has a mass ratio of the glass fiber sizing agent, i.e., ignition loss, of 0.2 to 3.0 mass% when the volatile substances are completely volatilized by applying the glass fiber sizing agent and drying it. If the ignition loss of the glass fiber sizing agent applied to the glass fiber surface is too small, the above-mentioned properties may not be fully exhibited. On the other hand, if the ignition loss of the glass fiber sizing agent applied to the glass fiber surface is too large, the above-mentioned properties are not improved despite an increase in the amount applied, which is not economical. The ignition loss is more preferably 1.0 to 2.0 mass%. The ignition loss of the glass fiber sizing agent on the glass fiber can be measured according to JIS R 3420 (2013) 7.3.2.
[0034] [Resin molding] Next, the resin molded product of the present invention will be described. The resin molded product of the present invention is characterized by containing the above-described glass fiber and a thermosetting resin.
[0035] The resin molded body of the present invention can be produced by the SMC method, in which a laminate formed by stacking sheets containing glass chopped strands and a thermosetting resin is pressed, or by the BMC method, in which a mixture formed by kneading glass chopped strands with a thermosetting resin compound is placed in a pot of a mold and pressed with a plunger to be molded under heat and pressure.
[0036] The content of the chopped strands in the resin molded body is preferably 10 to 40% by mass. If the content of the chopped strands is too low, the content of the chopped strands may be insufficient, and the reinforcing effect may not be sufficient. On the other hand, if the content of the chopped strands is too high, the chopped strands and the thermosetting resin may not be uniform, or the shape of the resin molded body may not be maintained. The content of the chopped strands is more preferably 15 to 30% by mass. EXAMPLES
[0037] The present invention will now be described with reference to examples, but the present invention is not limited to these examples.
[0038] <Production of quaternary ammonium salts> Manufacturing Example 1 342.2g of coconut alkyl diethanolamine was placed in a 500mL four-neck flask, and the temperature was raised to 80°C under nitrogen bubbling. 157.8g of diethyl sulfate was then added dropwise from the dropping funnel over 120 minutes. After the dropwise addition, the mixture was allowed to react for 60 minutes to obtain a yellow to reddish brown transparent liquid containing dihydroxyethyl ethyl cocoalkyl ammonium ethyl sulfate. The reaction rate (quaternization rate) in this reaction was 85%.
[0039] Manufacturing Example 2 A 500 mL four-neck flask was charged with 338.0 g of lauryldiethanolamine, and the temperature was raised to 80° C. under nitrogen bubbling, and then 162.0 g of diethyl sulfate was added from a dropping funnel in the same manner as in Production Example 1, to obtain a yellow to reddish brown transparent liquid containing dihydroxyethyl ethyl lauryl ammonium ethyl sulfate. The reaction rate (quaternization rate) in this reaction was 85%.
[0040] Production Example 3 A yellow to reddish brown transparent liquid containing dipolyoxyethylene ethyl cocoalkyl ammonium ethyl sulfate was obtained in the same manner as in Production Example 1, except that 354.9 g of polyoxyethylene (5) cocoalkylamine and 144.8 g of diethyl sulfate were mixed in a 500 mL four-neck flask. The reaction rate (quaternization rate) in this reaction was 100%.
[0041] Production Example 4 A yellow to reddish brown transparent liquid containing dipolyoxyethylene ethyl cocoalkyl ammonium ethyl sulfate was obtained in the same manner as in Production Example 1, except that 438.0 g of polyoxyethylene (20) cocoalkylamine and 59.1 g of diethyl sulfate were mixed into a 500 mL four-neck flask. The reaction rate (quaternization rate) in this reaction was 100%.
[0042] Production Example 5 A yellow to reddish brown transparent liquid containing dipolyoxyethylene ethyl tallow alkyl ammonium ethyl sulfate was obtained in the same manner as in Production Example 1, except that 439.4 g of polyoxyethylene (20) tallow alkyl amine and 60.6 g of diethyl sulfate were mixed in a 500 mL four-neck flask. The reaction rate (quaternization rate) in this reaction was 100%.
[0043] <Preparation of glass fiber sizing agent> Example 1 The quaternary ammonium sulfate was 0.8 mass% dihydroxyethyl ethyl cocoalkylammonium ethyl sulfate obtained in Production Example 1, the polyvinyl acetate resin Movinyl 350 (manufactured by Japan Coating Resins Co., Ltd.) was 10 mass% (solids content equivalent, the same applies below), the polyurethane resin Bondic 2220 (manufactured by DIC Corporation) was 1 mass%, and the silane coupling agent A-174 (manufactured by Momentive Performance Materials Japan, LLC) was 0.5 mass% in deionized water to prepare glass fiber sizing agent 1.
[0044] Example 2 Glass fiber sizing agent 2 was prepared in the same manner as in Example 1, except that dihydroxyethyl ethyl lauryl ammonium ethyl sulfate obtained in Production Example 2 was used as the quaternary ammonium sulfate.
[0045] Example 3 Glass fiber sizing agent 3 was prepared in the same manner as in Example 1, except that dipolyoxyethylene (n=2, m=3) ethyl cocoalkyl ammonium ethyl sulfate obtained in Production Example 3 was used as the quaternary ammonium sulfate.
[0046] Example 4 Glass fiber sizing agent 4 was prepared in the same manner as in Example 1, except that dipolyoxyethylene (n, m = 10) ethylstearylammonium ethyl sulfate obtained in Production Example 4 was used as the quaternary ammonium sulfate.
[0047] Example 5 Glass fiber sizing agent 5 was produced in the same manner as in Example 1, except that dihydroxyethyl ethylstearyl ammonium ethyl sulfate obtained in Production Example 5 was used as the quaternary ammonium sulfate.
[0048] Comparative Example 1 Glass fiber sizing agent 6 was prepared in the same manner as in Example 1, except that lauryl dimethyl ethyl ammonium ethyl sulfate was used as the quaternary ammonium sulfate.
[0049] Comparative Example 2 Glass fiber sizing agent 7 was prepared in the same manner as in Example 1, except that octyldimethylethylammonium ethyl sulfate was used as the quaternary ammonium sulfate.
[0050] Glass fiber sizing agents 1 to 7 were applied to a glass fiber monofilament having an average diameter of 13 μm with an applicator so that the ignition loss was 1.0 mass%, and 300 glass fiber monofilaments were bundled into one to obtain a glass fiber. The glass fiber was then wound as a cake on a collet, and the glass fiber sizing agent applied to the glass fiber was dried at a temperature of 140° C. for 10 hours, after which the glass fiber was taken out of the cake, bundled, and wound to obtain a glass roving strand with a count of 4800 tex. Next, the glass roving strand was cut to obtain a chopped strand with a length of 25 mm.
[0051] The amount of charge on the chopped strands and the appearance color of a resin molded product produced using the chopped strands were evaluated by the following methods. The results are shown in Table 1. The amount of charge was measured by measuring the charged voltage of the chopped strands one minute after the glass fibers had been cut using a static electricity measuring device, Statiron DZ4 (manufactured by Shishido Electrostatic Corporation). The appearance color was evaluated by visually inspecting the appearance of a resin molded body produced by the SMC method using a bathtub compound (75% by mass) made of unsaturated polyester resin, calcium carbonate, and aluminum hydroxide, and a sheet made of chopped strands (25% by mass). If the desired color was obtained as a result of the visual inspection, it was marked with "◯", and if the desired color was not obtained, it was marked with "X".
[0052] [Table 1]
[0053] As shown in Table 1, the chopped strands of Examples 1 to 6 all had excellent antistatic properties and appearance. In contrast, the chopped strands of Comparative Examples 1 and 2 did not have sufficient antistatic properties.
Claims
1. A reaction product of lauryldiethanolamine, coconut alkyldiethanolamine, or polyoxyethylene coconut alkylamine with diethyl sulfate, Contains a quaternary ammonium salt represented by the following general formula (1): An antistatic agent for glass fibers, comprising the above reactant which is liquid at room temperature. 【Chemistry 1】 (In the formula, R 1 represents an alkyl or alkenyl group having 8 to 22 carbon atoms; R 2 R represents an ethyl group, m and n represent the average number of moles of ethyleneoxy groups added, each independently being a number of 0.5 to 10. 3 indicates an ethyl group.)
2. A sizing agent for glass fibers, comprising the antistatic agent for glass fibers according to claim 1.
3. The glass fiber sizing agent according to claim 2, further comprising a film-forming agent, a lubricant and a silane coupling agent.
4. 4. A glass fiber comprising a plurality of glass fiber monofilaments and a coating formed by applying the glass fiber sizing agent according to claim 2 or 3 to the glass fiber monofilaments.
5. A resin molding comprising the glass fiber according to claim 4 and a thermosetting resin.
Citation Information
Patent Citations
JP1959-000079B
Apparatus for supplying printer ink ribbon
JP1987042870A
The first ammonium antistatic compound 4
JP1992502911A
Motor controlling circuit and motor controller
JP1993030780A
Glass fiber chemical treatment composition having good stability emulsified epoxy and treated glass fiber
JP1995505658A
